Organizational Injustice and Police Misconduct: Predicting Organizational Defiance Among Police Officers - P. D. Reynolds; R. C. Helfers (Russian Journal of Economics and Law)
Objective: to research the influence of organizational injustice on police misconduct in the United States of America. Methods: dialectic approach to the cognition of social phenomena, allowing to analyze them in the historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, sociological.Results: numerous researches support the association between organizational justice and employee performance. This study utilizes organizational justice as a theoretical framework to predict self-reported police misconduct. In particular, this study builds upon recent work into police officers' behavioral responses to perceived injustice by exploring the link between perceptions of overall organizational injustice and three forms of police defiance: 1) using departmental rules, policies, or laws against the administration when needed, 2) purposely undermining the administration's goals, and 3) disregarding organizational policies and procedures. Data was collected using an online self-report survey distributed to a convenience sample of sworn police officers that were members of a police officer association in a southern state.Scientific novelty: for the first time, the work analyzes the impact of organizational injustice on police defiance. Multinomial logistical regression techniques were used for analyses, suggesting that perceived overall injustice has a positive effect on the likelihood officers would self-report engaging in all three forms of organizational defiance, namely: 1) using departmental rules, policies, or laws against the administration when needed, 2) purposely undermining the administration's goals, and 3) disregarding organizational policies and procedures.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activity when viewing and studying the issues related to the impact of organizational injustice on disciplinary breaches of police officers.